Makna Shihāb dalam Tafsir Kemenag - Dhemira Dahlan; Nurul Istiqomah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
The interpretative paradigm occurs when the development of knowledge in various aspects. One of them happened in the interpretations issued by the Ministry of Religion. The discussion about the word shihāb provides a sharp spotlight for research. Even though it is still within the scope of the interpretation of the Ministry of Religion, it does not rule out the possibility of differences in interpretation because there are certain factors that surround it. The purpose of this paper is to dissect how the construction of interpretation and the dynamic process related to the word shihāb in the interpretation of the Ministry of Religion. Using the method of library research (Library Research) and a descriptive-qualitative approach, this paper will describe the development of the interpretation of the word shihāb in the Interpretation of the Ministry of Religion. The interpretations taken in this paper are the Al-Qur'an and its Translation, the Qur'an and its Interpretations (Tafsir Tahlili), Abridged Tafsir of Al-Qur'an al-Karim (Tafsir Wajiz), as well as several studies of scientific interpretations of the same theme. As for the results of this paper regarding the word shihāb, there is a shift in interpretation based on the period of production of the Ministry of Religion's interpretation of production. Originally the word shihāb was interpreted with theological elements.